Planning and design for future informal settlements : shaping the self-constructed city - Gouverneur, David (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2015)
'This is the first book to address future informal settlements at the global scale. It argues that to foster favourable conditions for the sustainable evolution of future informal cities, planners must consider the same issues that are paramount in formal urban developments, such as provision of:balanced land usesenergy efficiency and mobility water management and food sufficiencygovernance and community participation productivity and competitiveness identity and sense of place Planning and Design for Future Informal Settlements makes a call for responsible action to address the urban challenges of the developing world, suggesting that the vitality of informality, coupled with spatial design and good management, can support the efficient use of resources in better places to live.The book analyses the strengths and weaknesses of informal urbanism and the challenges faced by the fast growing cities of the developing world. Through case studies, it demonstrates the contributions and limitations of different attempts to plan ahead for urban growth, from the creation of formal housing and urban infrastructures for self-built dwellings to the improvement of existing informal settlements. It provides a robust framework for planners and designers, policy-makers, NGOs and local governments working to improve living conditions in developing cities'--
'This is the first book to address future informal settlements at the global scale. It argues that to foster favourable conditions for the sustainable evolution of future informal cities, planners must consider the same issues that are paramount in formal urban developments, such as provision of: - balanced land uses - energy efficiency and mobility - water management and food sufficiency - governance and community participation - productivity and competitiveness - identity and sense of place Planning and Design for Future Informal Settlements makes a call for responsible action to address the urban challenges of the developing world, suggesting that the vitality of informality, coupled with spatial design and good management, can support the efficient use of resources in better places to live. The book analyses the strengths and weaknesses of informal urbanism and the challenges faced by the fast growing cities of the developing world. Through case studies, it demonstrates the contributions and limitations of different attempts to plan ahead for urban growth, from the creation of formal housing and urban infrastructures for self-built dwellings to the improvement of existing informal settlements. It provides a robust framework for planners and designers, policy-makers, NGOs and local governments working to improve living conditions in developing cities'--
Includes bibliographical references (pages 269-278) and index.
Keywords: Squatter settlements -- Developing countries; City planning -- Developing countries; Urban policy -- Developing countries